Taffix® Nasal Powder Spray Forms an Effective Barrier Against Infectious New Variants of SARS-Cov-2 (Alpha, Beta and Delta) - Mandelboim, Michal; Mendelson, Ella; Drori, Yaron; Atari, Nofar; Lapidot, Tair; Megiddo, Dalia; Gladnikoff, Micha (Archives of Clinical and Biomedical Research, 2021)
While vaccination efforts against SARS-CoV-2 around the world are ongoing, new highly infectious virus variants continue to evolve. The protection provided by the available vaccines against some of the new variants is weaker. Additional preventive measures will therefore be needed to protect the population until effective vaccinations are widely available. TaffiX® is an anti-viral nasal powder spray comprised of low-pH hypromellose, which forms a protective mechanical barrier that prevents viruses from engaging with nasal cells. The current study aimed to test the protective effect of TaffiX® against SARS-CoV-2 Alpha (B.1.1.7; hCoV-19/Israel/CVL-46879-ngs/ 2020), Beta, (B.1.351; hCoV-19/Israel/CVL-2557-ngs/2020) and Delta (B.1.617.2; hCoV-19/Israel/ VVL-12806/2021), three highly infectious and pathogenic SARS-CoV-2 strains. A nylon filter was treated with Taffix® gel, after which SARS-CoV-2 Alpha, Beta or Delta was seeded. After a 10-min incubation, the downstream side of each filter was washed, and the rinse was collected and placed over Vero-E6 cells. After 5 days of incubation, viral RNA was extracted and subjected to SARS-CoV-2 RT-PCR analysis. Taffix® fully blocked passage of all three tested SARS-CoV-2 variants, as demonstrated by a 100% reduction of recoverable viral RNA from Vero-E6 cells, as compared to cells treated with rinse from filters not treated with Taffix(R). These results support its use as an effective barrier against new variants of SARS-CoV-2 in conjunction with other protective measures.